PENERAPAN MODEL DISCOVERY LEARNING UNTUK MENINGKATKAN KERJASAMA DAN PRESTASI BELAJAR (Studi Pada Mata Pelajaran Biologi Siswa Kelas XI IPA SMA Negeri 3 Pagar Alam) - Siti Gadis Pertiwi (DIADIK, 2021)
This research aims to describe the application of the Discovery Learming Model to improve cooperation and student achievement in Biology subjects in class XI IPA SMA Negeri  3 Pagaralam This research was conducted using Classroom Action Research (CAR) and quasi-experimental. Data collection methods in this study used observation sheets to measure the learning process and student cooperation and to measure student achievement using tests. CAR was carried out in class XI IPA. Experiments in class XI IPA.4 and Control in class XI IPA.1. Data analysis for CAR uses the t test. Meanwhile, for quasi experiments using the normality test, homogeneity, and t test. The results show that the application of the Discovery Leaming model can improve cooperation  and si's learning achievement  self as seen from the teacher's ability to implement the learning model, namely in the first cycle it was in the poor category, in the second cycle it was good, and in the third cycle it was very good.  Student collaboration data showed an increase, namely in the first cycle the category was poor, in the second cycle the category was good, and in the third cycle it was categorized as very good.  The achievement value in the first cycle is 61.69, the second cycle is 71.96 and the third cycle is 83.62.  The post-test scores for cycles I and II have not yet achieved classical completeness because s is 85% and cycle III has reached classical completeness  85%.  This study resulted in the conclusion that the application of the Discovery Leaming model can improve cooperation and student achievement in Biology subjects